Diffusion-weighted MRI of epithelial ovarian cancers: Correlation of apparent diffusion coefficient values with histologic grade and surgical stage. Issue 4 (April 2015) - Oh, Ji-Won; Rha, Sung Eun; Oh, Soon Nam; Park, Michael Yong; Byun, Jae Young; Lee, Ahwon
Highlights: The solid component of all invasive epithelial cancers showed high b 1000 signal intensity. ADCs can predict the histologic grade of epithelial ovarian cancer. ADCs correlate negatively to the surgical stage of epithelial ovarian cancer. ADCs may be useful imaging biomarkers to assess epithelial ovarian cancer. Abstract: Objective: The purpose of this article is to correlate the apparent diffusion coefficient (ADC) values of epithelial ovarian cancers with histologic grade and surgical stage. Materials and methods: We enrolled 43 patients with pathologically proven epithelial ovarian cancers for this retrospective study. All patients underwent preoperative pelvic magnetic resonance imaging (MRI) including diffusion-weighted images with b value of 0 and 1000 s/mm 2 at 3.0-T unit. The mean ADC values of the solid portion of the tumor were measured and compared among different histologic grades and surgical stages. Results: The mean ADC values of epithelial ovarian cancers differed significantly between grade 1 (well-differentiated) and grade 2 (moderately-differentiated) ( P  = 0.013) as well as between grade 1 and grade 3 (poorly-differentiated) ( P  = 0.01); however, no statistically significant difference existed between grade 2 and grade 3 ( P  = 0.737). The receiver-operating characteristic analysis indicated that a cutoff ADC value of less than or equal to 1.09 × 10 −3  mm 2 /s was associated with 94.4% sensitivity and 85.7% specificity in distinguishing grade 1 and grade 2/3 cancer. The difference in mean ADC values was statistically significant for early stage (FIGO stage I) and advanced stage (FIGO stage II-IV) cancer ( P  = 0.011). The interobserver agreement for the mean ADC values of epithelial ovarian cancers was excellent. Conclusion: The mean ADC values of the solid portion of epithelial ovarian cancers negatively correlated to histologic grade and surgical stage. The mean ADC values may be useful imaging biomarkers for assessment of tumor grade of epithelial ovarian cancer.